Apakah Status Akreditasi Rumah Sakit Memberikan Perbedaan Pemberian Obat yang Benar dan Keselamatan Pasien? - Putro, Saptono; Wardhani, Viera; Siswanto, Siswanto (Media Kesehatan Masyarakat Indonesia, 2018)
Hospital accreditation provides guidelines for implementing quality management standards including drug management management to reduce the incidence of patient safety (IPS). This study aims to determine the difference between the right implementation of drug administration and the perceieved of IPS based on hospital accreditation status. This researchusing a survey method with cross sectional analytical approach, which compares the correct implementation of the drug and IKP perception in 2 type D hospitals with different accreditation status in the Greater Malang area. Measurements of the correct implementation of drug administration and IKP perceptions were carried out using a closed questionnaire on 36 nurses and 99 primary hospital patients and 41 nurses and 96 full hospital patients. Analysis was carried out by Mann Whitney Z test and Rank Spearman test. Both hospitals showed the correct level of implementation of good drug delivery and low IPS perception even though the first accredited hospital showed a better picture than plenary accredited hospitals. In hospitals with initial accreditation shows that the better the right implementation of drug administration, the lower the perception of IPS according to nurses and patients. There was no similar relationship in the hospital with full accreditation status, where there was no difference in the level of true implementation of drug administration and IKP perception according to nurses and patients.